2007
DOI: 10.1152/ajpcell.00085.2006
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy, but not necrosis, in rabbit skeletal muscle denervated for periods up to one year

Abstract: JC. Atrophy, but not necrosis, in rabbit skeletal muscle denervated for periods up to one year. Am J Physiol Cell Physiol 292: C440 -C451, 2007; doi:10.1152/ajpcell.00085.2006.-Our understanding of the effects of long-term denervation on skeletal muscle is heavily influenced by an extensive literature based on the rat. We have studied physiological and morphological changes in an alternative model, the rabbit. In adult rabbits, tibialis anterior muscles were denervated unilaterally by selective section of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 55 publications
6
70
0
7
Order By: Relevance
“…Moreover, the fiber and whole-muscle average decreases in CSA were similar in magnitude to the wet musculotendon mass data for both the LDE and CT muscles (Fig.3). In hibernating bears, this consistency indicates that the musculotendon complex composition and structure did not change drastically, such as in the case of replacement of contractile tissue with connective tissue and/or fat, which can occur following denervation (Tews et al, 1994;Ashley et al, 2007). In summeractive bears, this consistency reflects that most of the muscle mass decrease was due to loss of the contractile components.…”
Section: Discussion Differences In the Effects Of Denervation Betweenmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the fiber and whole-muscle average decreases in CSA were similar in magnitude to the wet musculotendon mass data for both the LDE and CT muscles (Fig.3). In hibernating bears, this consistency indicates that the musculotendon complex composition and structure did not change drastically, such as in the case of replacement of contractile tissue with connective tissue and/or fat, which can occur following denervation (Tews et al, 1994;Ashley et al, 2007). In summeractive bears, this consistency reflects that most of the muscle mass decrease was due to loss of the contractile components.…”
Section: Discussion Differences In the Effects Of Denervation Betweenmentioning
confidence: 87%
“…However, we chose to section the common peroneal, which innervates the dorsiflexors, for three reasons: (1) the surgery was minimally invasive as the nerve is superficial, thus minimizing any local tissue damage (e.g. scarring) or the potential of affecting hibernation behavior; (2) previous studies have measured the seasonal changes in the dorsiflexors of hibernating wild black bears (Harlow et al, 2001;Lohuis et al, 2007), which provides a baseline from which to compare the results of this study; and (3) previous studies in other mammals have shown that denervation of the dorsiflexors produces gross atrophy (Dedkov et al, 2003;Ashley et al, 2007).…”
Section: Materials and Methods Bear Population And Hibernation Conditmentioning
confidence: 99%
See 1 more Smart Citation
“…If, however, later stages of denervation are examined there are indications (although no hard evidence) of differences between muscles and species particularly in the time course of the atrophy (i.e. alteration after a few months in rat can be observed up to one year in humans) [2,6,52]. Skeletal muscle atrophy involves many protein systems; in this review we will focus on the more relevant changes of the excitation-contraction coupling, ECC, and mechano-transduction observed in early-and long-term denervated skeletal muscles.…”
Section: Excitation-contraction Coupling In Denervated Musclementioning
confidence: 99%
“…It progresses during the first two years of denervation, while severe atrophy (a stage in which muscle fiber size decreases to 20-10% with respect to normal values) appears after twothree years, accompanied by a progressive degeneration of the muscle tissue [4,5]. This behaviour is not unique to humans, but it is a common feature in mammals larger than rodents [6,7].…”
Section: Introductionmentioning
confidence: 99%